Technological Microbiology: Development and Applications - Vitorino, Luciana C.; Bessa, Layara A. (Frontiers in Microbiology, 2017)
Over thousands of years, modernization could be predicted for the use of microorganisms in the production of foods and beverages. However, the current accelerated pace of new food production is due to the rapid incorporation of biotechnological techniques that allow the rapid identification of new molecules and microorganisms or even the genetic improvement of known species. At no other time in history have microorganisms been so present in areas such as agriculture and medicine, except as recognized villains. Currently, however, beneficial microorganisms such as plant growth promoters and phytopathogen controllers are required by various agricultural crops, and many species are being used as biofactories of important pharmacological molecules. The use of biofactories does not end there: microorganisms have been explored for the synthesis of diverse chemicals, fuel molecules, and industrial polymers, and strains environmentally important due to their biodecomposing or biosorption capacity have gained interest in research laboratories and in industrial activities. We call this new microbiology Technological Microbiology, and we believe that complex techniques, such as heterologous expression and metabolic engineering, can be increasingly incorporated into this applied science, allowing the generation of new and improved products and services.